PENGARUH PROPORSI KEPEMILIKAN INSTITUSIONAL INDUSTRI MANUFAKTUR INDONESIA TERHADAPDISCRETIONARY ACCRUALS MODEL JONES MODIFIKASI DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Cahyo Indraswono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
This study aimed to get empirical evidence about the influence of ownership structureinstitutionalmanufacture industry company on earnings management with the firm size as a moderating variable in the relationship between ownership structure company and discretionary accruals earnings management model Jones Modified. This research was carried out by using a sample of one hundred and fiveIndustri manufaktur companies listed on the Indonesian Stock Exchange (IDX) in 2012-2014. One indicator of corporate performance assessment is the amount of compensation received by the manager, where this can be the motivation of earnings management action. Earnings management measures can be minimized by monitoring the management by using the proportion of ownership by outsiders in the company.Earnings management is measured using the modified Jones models with discretionary accruals as a proxy for earnings management. Statistical test equipment used in this research is multiple regression. This study obtained evidence that the structure of institutional ownership manufacture industry company has a significant negative effect on discretionary accruals earnings management, while the firm size is not able to moderate the influence of ownership structure manufacture industry on discretionary accruals earnings management of the company. This occurs because the IDX stock market ishave a capital market with companies that have large asset value so that the size of the company is not able to streng then the influence of ownership structure on earnings management action.Keywords: Ownership StructureManufacture Industry, Firm Size, Discretionary Accruals Earnings Management and Modified Jones Model.